An incredible journey : the story of Alcock and Brown - "Sloan, Carolyn" (Franklin Watts New York, 1992)
The first title in a series about key moments in history, this recalls the dramatic events of Alcock and Brown's epic journey across the Atlantic, non-stop, by aeroplane.